Influence of process parameters on hot tensile behavior of rotary friction welded In 718/AISI 410 dissimilar joints. (November 2021) - J, Alex Anandaraj; Rajakumar, S; Balasubramanian, V; Kavitha, S
Highlights: Effect of rotary friction welding parameters was discussed by mechanical and metallurgical aspects. Rotational speed is found as an influencing process parameter among other RFW parameters. Evaluated room and elevated temperature properties on dissimilar joints. Weld failure characteristics were analyzed and detailed in the dissimilar joints. Graphical Abstract: ga1 Abstract: The dissimilar joints are adopted to enhance the functionality of components and improve the working limits in critical applications like nuclear power plants and gas turbines. This investigation studied the influence of process parameters on dissimilar joining of Inconel 718 and AISI 410 martensitic stainless steel by Rotary Friction Welding (RFW) process. The major welding parameters of RFW were Rotational Speed, Friction pressure, Forging pressure, Friction time, and Forging time. Among these welding parameters, the joint strength was influence by the rotational speed. The evaluated tensile and microhardness properties were correlated with microstructures. The hot tensile properties result that the strength decreased with an increasing the operating temperature. The weld failure occurred in both a weld interface and thermomechanical affected zone, which is due to the formation of martensite and intermetallic.